Toxicological Effects of Ethanolic Stem Bark Extract of Xylopia Aethiopica on Testicular Oxidative Stress Markers and Histology of Male Rats - Elias Adikwu; Ben Ehigiator (Biology, Medicine, & Natural Product Chemistry, 2020)
Impairment in testicular function can occur through perturbations in testicular oxidative stress markers and histology. Xylopia aethiopica (XE) is used to enhance fertility in males, but with information gap on its effect on testicular oxidative stress markers and histology. The present study assessed the effects of ethanolic stem bark extract of Xylopia aethiopica (EEXA) on testicular oxidative stress markers and histology of male albino rats. Sixty adult male albino rats (200g-250g) were randomly grouped into 4 (A-D) of 15 rats per group. The rats in the control group A (A1-A3) were administered per oral (p.o) with water (0.2 mL/day) for 15, 30 and 60 days respectively. The rats in groups B (B1-B3), C(C1-C3) and D (D1-D3) were administered p.o with EEXA (200, 400 and 800 mg/kg/day) for 15, 30 and 60 days respectively. The rats were anesthetized at the termination of EEXA administration and were dissected and testes removed. The testes were weighed and evaluated for oxidative stress markers and histology. Testicular weights were decreased in a dose and-time dependent fashion in EEXA-treated rats. Significant decreases in testicular superoxide dismutase, glutathione, catalase, and glutathione peroxidase levels with significant increases in malondialdehyde levels in a dose and time-dependent fashion were observed in rats administered with EEXA. Testicular histology showed cellular necrosis, degeneration and loss of interstitial tissues in rats administered with EEXA. This study observed that EEXA perturbed testicular oxidative markers and histology. Its use may impair testicular function.